Comparative study between sugarcane bagasse and green coconut fiber in the purification of glycerin obtained from biodiesel synthesis - Velloso, Marcia Helena Rodrigues; Peruch, Kamila Felipe Campagnaro (Brazilian Journal of Production Engineering, 2021)
The search for renewable energy sources has increased the demand for biodiesel directly impacting the availability of glycerin obtained as a by-product of its production. In order to avoid the accumulation of this glycerin and make biodiesel synthesis more competitive, increasing the added value of this by-product, this study proposed the treatment of glycerin with phosphoric acid followed by purification with adsorbent. A comparative analysis was performed between the results obtained using sugar cane bagasse and green coconut fiber as adsorbents. It was observed that the highest glycerol content is obtained when using green coconut fiber, reaching approximately 89%. The purity achieved is feasible for application in animal feed and in biotechnological processes.